Characteristics of Pc5 activity at high latitudes stations in Antarctica. (15th October 2019) - Kwon, Hyuck-Jin; Kim, Khan-Hyuk; Jee, Geonhwa; Jin, Ho; Kim, Hyomin; Shin, Jehyuck; Lee, Seungah; Kwon, Jong-Woo; Kim, Jeong-Han; Lee, Changsup; Lessard, Marc
Abstract: We examined wave activities in the Pc5 frequency band (~2–7 mHz) using the magnetic field data from five Antarctic stations, which are AGO3 (72.5° S Altitude-Adjusted Corrected Geomagnetic latitude), South Pole (SPA, 74.6° S), McMurdo (MCM) and Jang Bogo Station (JBS, 80° S), and Dome C (DMC, 89.1° S), during 2017. Pc5 waves at AGO3 and SPA show characteristics associated with Kelvin-Helmohltz instability on the magnetopause and substorm activities, under closed field lines conditions. The local time and seasonal dependence of Pc5 wave activities at polar cap stations (MCM, JBS, and DMC) are significantly different from those at AGO3 and SPA. These indicate that the generation mechanism of Pc5 activities in the open field line region at polar cap is different from that in the closed field lines. We suggest that polar-cap Pc5 is generated by ionospheric current variations produced by solar dynamo between solar wind plasma and geomagnetic field. Highlights: Pc5 pulsations observed at high latitude ground stations located in Antarctica in 2017. Latitudinal dependence of diurnal seasonal variations of Pc5 activities. The comparison of Pc5 and solar wind speed. Difference generation mechanism of Pc5 waves at auroral latitudes and polar-cap region.